Inverse Occlusion: A Binocularly Motivated Treatment for Amblyopia - Jiawei Zhou; Zhifen He; Yidong Wu; Yiya Chen; Xiaoxin Chen; Yunjie Liang; Yu Mao; Zhimo Yao; Fan Lu; Jia Qu; Robert F. Hess (Neural Plasticity)
Recent laboratory findings suggest that short-term patching of the amblyopic eye (i.e., inverse occlusion) results in a larger and more sustained improvement in the binocular balance compared with normal controls. In this study, we investigate the cumulative effects of the short-term inverse occlusion in adults and old children with amblyopia. This is a prospective cohort study of 18 amblyopes (10-35 years old; 2 with strabismus) who have been subjected to 2 hours/day of inverse occlusion for 2 months. Patients who required refractive correction or whose refractive correction needed updating were given a 2-month period of refractive adaptation. The primary outcome measure was the binocular balance which was measured using a phase combination task; the secondary outcome measures were the best-corrected visual acuity which was measured with a Tumbling E acuity chart and converted to logMAR units and the stereoacuity which was measured with the Random-dot preschool stereogram test. The average binocular gain was 0.11 in terms of the effective contrast ratio (z=−2.344, p=0.019, 2-tailed related samples Wilcoxon Signed Rank Test). The average acuity gain was 0.13 logMAR equivalent (t17=4.76, p<0.001, 2-tailed paired samples t-test). The average stereoacuity gain was 339 arc seconds (z=−2.533, p=0.011). Based on more recent research concerning adult ocular dominance plasticity, we conclude that inverse occlusion in adults and old children with amblyopia does produce long-term gains to binocular balance and that acuity and stereopsis can improve in some subjects.